Використання в декоративному садівництві України інтродукованих видів родини Scrophulariaceae Juss. - Prokopchuk, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
As the result of analysis of potential capabilities of 22 species of flower decorative plants from Scrophulariaceae family, variants of their usage as perspective species for enrichment of taxonomic contents and quantitative structure of the national plant assortment for flower arrangement were offered.